ACCOUNTANTS IN OPA. - Halterman, J. F. (The Accounting Review, 1944)
Abstract The article presents information on the accountants in the Office of Price Administration (OPA). The operation of OPA are divided into two parts, the national office in Washington D.C. and the offices in the field. In the national office, interest is primarily directed toward preparation of regulations, formulation of general over-all Policy; making surveys on a national scale of those commodities subject to price control, post-auditing the decisions of the regional office and in certain instances, handling some price adjustment. The Accounting Division in its national office and field operations acts more as an integrated unit than do the operating departments. Within this division, there are also certain well-defined areas of authority and responsibility; but the individual offices come to the aid of each other whenever it is necessary and convenient. Personnel of the national office will come to the assistance of the District Accountant and District Accountants have sent members of their staffs to another district for short periods.